Recovery of Al, Cr and V from steel slag by bioleaching: Batch and column experiments. (15th September 2018) - Gomes, Helena I.; Funari, Valerio; Mayes, William M.; Rogerson, Mike; Prior, Timothy J.
Abstract: Steel slag is a major by-product of the steel industry and a potential resource of technology critical elements. For this study, a basic oxygen furnace (BOF) steel slag was tested for bacterial leaching and recovery of aluminium (Al), chromium (Cr), and vanadium (V). Mixed acidophilic bacteria were adapted to the steel slag up to 5% (w/v). In the batch tests, Al, Cr, and V were bioleached significantly more from steel slag than in control treatments. No statistical difference was observed arising from the duration of the leaching (3 vs 6 d) in the batch tests. Al and Cr concentrations in the leachate were higher for the smaller particle size of the steel slag (<75 μm), but no difference was observed for V. In the column tests, no statistical difference was found for pH, Al, Cr and V between the live culture (one-step bioleaching) and the supernatant (two-step bioleaching). The results show that the culture supernatant can be effectively used in an upscaled industrial application for metal recovery. If bioleaching is used in the 170–250 million tonnes of steel slag produced per year globally, significant recoveries of metals (100% of Al, 84% of Cr and 8% of V) can be achieved, depending on the slag composition. The removal and recovery percentages of metals from the leachate with Amberlite ® IRA-400 are relatively modest (<67% and <5%, respectively), due to the high concentration of competing ions (SO4 2−, PO4 3− ) in the culture medium. Other ion exchange resins can be better suited for the leachate or methods such as selective precipitation could improve the performance of the resin. Further research is needed to minimise interference and maximise metal recovery. Graphical abstract: Image 1 Highlights: Bioleaching of Al, Cr and V was significantly higher than the control. Lower particle size (<75 μm) significantly increased bioleaching of Al and Cr. There was no statistical difference between 3-day and 6-day leaching. Life culture and the supernatant had a similar performance in columns. Secondary bioleaching could be used to recover metals from steel slag.